Genetic diversity and matrilineal genetic origin of fat-rumped sheep in Ethiopia - Nigussie, Helen; Mwacharo, Joram M.; Osama, Sarah; Agaba, Morris; Mekasha, Yoseph; Kebede, Kefelegn; Abegaz, Solomon; Pal, Sanjoy K. (Springer, 2019)
Ethiopia is home to a diverse gene pool of indigenous sheep populations. Therefore, a better understanding of genetic variation holds the key to future utilization through conservation. Three of these breeds, Afar, Blackhead Somali, and Hararghe Highland, are found in eastern Ethiopia where they contribute significantly to the livelihood of most pastoralist, agro-pastoralist, and smallholder farmers. These indigenous sheep are recognized on the basis of morphotype and their genetic distinction remains unknown. Here, to assess genetic variation, and matrilineal genetic origin and relationship of fat-rumed sheep found in eastern Ethiopia, 300 individuals from the three breeds were genotyped for 22 microsatellite markers and sequenced for the mitochondrial DNA displacement loop (mtDNA d-loop) region. The overall HO and HE were 0.57 and 0.75, respectively. Differentiation statistics revealed that a high proportion (97%) of the total genetic variation was explained by differences between individuals within populations. Genotype assignment independent of the population of origin showed K = 2 to be the optimum number of genetic backgrounds present in the dataset. This result was further confirmed by mtDNA D-loop sequences comparison in which the matrilineal genetic origin of eastern Ethiopia sheep is from two haplotype groups (types A and B) among the five haplotypes globally observed. Taken together, our findings suggest that the sheep populations from three breeds originated from two ancestral genetic backgrounds that may have diverged prior to their introduction to Ethiopia. However, to obtain a complete picture of the evolutionary dynamics of Ethiopian indigenous sheep, more samples and populations from within and outside of the country will need to be analyzed.